Effect of Fertilizers and Pesticides Application On Soil Microbiota - Mohanty, Suchismita; Dash, Subhaprada (International Journal of Psychosocial Rehabilitation, 2025)
Soil health management is vital to guarantee production of sustainable agriculture and biodiversity maintenance. Modern farming relies primarily on the extensive use of agrochemicals, including inorganic pesticides and fertilizers. Arbitrary, long-term and over-use of pesticides has serious effects on soil ecology that can lead to changes in or degradation of valuable or crop probiotic soil microbiota. For industrial agriculture, pesticides and fertilizers are a necessary evil. In addition to a number of broadly discussed and well-known harmful effects on the human health and environment of chemical fertilizers and pesticides, they were also held responsible for strongly affecting soil microbial properties. Soil microbiota is a key component of agricultural ecosystems, which not only plays an important role in basic soil processes, but also actively participates in improving the productivity of crop and soil fertility. Pesticides and fertilizers continue to remain in the soil for a long time so they are expected to affect the micobiota of the soil and thus disturbing the health of the soil. This study reviews the effect of long-term use of pesticides and fertilizers on cultivated soil microbiota with respect to fertility and soil health.